Management Information System For Garuda Cooperatives, Sragen - Fahrizal Surya Panuntun; Ahmad Subhan Yazid; Muhammad Mustakim (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2015)
The need for information in life has transformed into basic needs. As an impact, this will cause problems when not handled properly. The Garuda Cooperative is one of the Employee Cooperatives in Sragen with complex managerial data but its management is still manual. To support its business process, a management information system is needed to handle data quickly and accurately. This study aims to develop a management information system for Garuda Cooperatives. The flow of research used is analysis, design, implementation, testing, and conclusion. System modeling uses the Unified Modeling Language (UML) in the form of a use case diagram and statechart diagram. The programming language used is Delphi with PostgreSQL as database management. The information system produced includes processing savings and loan business units, processing membership data and reports. The results of the system testing on 8 respondents showed that the system was running well to meet needs, had an attractive appearance, and was easy to use.